Probability - With Applications and R (2nd Edition) - Wagaman, Amy S.; Dobrow, Robert P. (John Wiley & Sons, 2021)
In the newly revised Second Edition of this book, distinguished researchers deliver a thorough introduction to the foundations of probability theory. The book includes a host of chapter exercises, examples in R with included code, and well-explained solutions. With new and improved discussions on reproducibility for random numbers and how to set seeds in R, and organizational changes, the new edition will be of use to anyone taking their first probability course within a mathematics, statistics, engineering, or data science program. New exercises and supplemental materials support more engagement with R, and include new code samples to accompany examples in a variety of chapters and sections that didn't include them in the first edition. The new edition also includes for the first time: A thorough discussion of reproducibility in the context of generating random numbers; Revised sections and exercises on conditioning, and a renewed description of specifying PMFs and PDFs; Substantial organizational changes to improve the flow of the material; Additional descriptions and supplemental examples to the bivariate sections to assist students with a limited understanding of calculus.